Respostas

A melhor resposta!
2014-06-23T17:43:53-03:00
Primeiro vamos deixá-la na forma padrão de equação:
x(2x+1)=5.3
2x²+x=15
2x²+x-15=0

Agora, só utilizar Bhaskara:
Δ=b²-4ac
Δ=1²-4.2.(-15)
Δ=1-8.(-15)
Δ=1+120
Δ=121

x=-b+-√Δ/2a
x=-1+-√121/2.2
x=-1+-11/4
x¹=-1+11/4 = 10/4 = 2,5
x²=-1-11/4 = -12/4 = -3
1 5 1
2014-06-23T21:05:59-03:00
x(2x+1)=5.3
2x²+x=15
2x²+x-15=0 
fazendo Bhaskara
Δ=b²-4ac
Δ=1²-4.2.(-15)
Δ=1-8.(-15)
Δ=1+120
Δ=121

x=-b+-√Δ/2a
x=-1+-√121/2.2
x=-1+-11/4
x'=-1+11/4 = 10/4 = 2,5
e
x"=-1-11/4 = -12/4 = -3